2022
DOI: 10.3390/pr10101991
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Bilberry Extract with Maltodextrin and Gum Arabic by Freeze-Drying: Formulation, Characterisation, and Storage Stability

Abstract: Anthocyanins are polyphenolic plant pigments associated with antioxidant and health-promoting properties. However, their application in the food industry is limited due to their poor stability. The purpose of this study was to encapsulate anthocyanin-rich bilberry (Vaccinium myrtillus L.) extract by freeze-drying and to investigate the effects of different wall materials and extract contents on the physicochemical and bioactive properties of the obtained encapsulates. Ethanolic bilberry extract was encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…The outcome in this study implied that the combination of maltodextrin and gum Arabic at 9:1 (w/w) was the most suitable mixture for microencapsulation of CPH extract rich in alkaloids. mg/100 g DS), while the previous work [37] also encapsulated anthocyanin-rich bilberry extract by the use of maltodextrin, gum Arabic, and their combination at a 1:1 w/w ratio and freeze-drying, which found that the mixture of bilberry solids to wall material ratios at 40:60 gained the maximum levels of TPC, total anthocyanins and antioxidant capacity after three-week storage at room temperature. These results implied that the powdered CPH extract rich in alkaloids in this study possessed high TAC (626.36 mg AE/g DS).…”
Section: Resultsmentioning
confidence: 98%
“…The outcome in this study implied that the combination of maltodextrin and gum Arabic at 9:1 (w/w) was the most suitable mixture for microencapsulation of CPH extract rich in alkaloids. mg/100 g DS), while the previous work [37] also encapsulated anthocyanin-rich bilberry extract by the use of maltodextrin, gum Arabic, and their combination at a 1:1 w/w ratio and freeze-drying, which found that the mixture of bilberry solids to wall material ratios at 40:60 gained the maximum levels of TPC, total anthocyanins and antioxidant capacity after three-week storage at room temperature. These results implied that the powdered CPH extract rich in alkaloids in this study possessed high TAC (626.36 mg AE/g DS).…”
Section: Resultsmentioning
confidence: 98%
“…Arabic gum is a natural source of fiber, carbohydrates (galactose and arabinose), and mineral salts (potassium, magnesium, and calcium). Because of its qualities, which include volatile retention, emulsification, low cost [ 65 ], negative charge properties, low viscosity, high solubility, convenience of use, inhibition of oxidation reactions, and colorlessness of solutions, this heteropolysaccharide is frequently employed as a coating material [ 66 , 67 ]. Syrups are mostly concentrated using it in the pharmaceutical industry [ 65 ].…”
Section: Natural Polymers Used For Encapsulationmentioning
confidence: 99%
“…Because of its qualities, which include volatile retention, emulsification, low cost [ 65 ], negative charge properties, low viscosity, high solubility, convenience of use, inhibition of oxidation reactions, and colorlessness of solutions, this heteropolysaccharide is frequently employed as a coating material [ 66 , 67 ]. Syrups are mostly concentrated using it in the pharmaceutical industry [ 65 ]. Because of its exceptional functional qualities and ability to remain stable in a variety of harsh conditions, it is utilized as a stabilizer in the food industry [ 67 ].…”
Section: Natural Polymers Used For Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that CHL are hydrophobic compounds and that the GA has a proteinous section, increasing its proportion led to producing an emulsion with higher stability followed by EE augmentation. GA due to its protein fraction can interact with the CHL and form a matrix-type structure that prevents the leakage and loss of CHL (Karaaslan et al, 2021;Todorović et al, 2022).…”
Section: -2-effect Of Wall Materials Proportions On the Microcapsulesmentioning
confidence: 99%